Fetal movements frequency Perceived by the Mother in the third quarter. - Jiménez A., José (2015)
This study concludes that: 1. The fetal activity showed an individual pattern, which remained more or less constant 1 during the third quarter, peaking in week 35. 2. an absolute number or range not found in the frequency of fetal movements perceived applicable to the third trimester of pregnancy.